Tetrabutylammonium 2,6-dihydroxybenzoate 2,6-dihydroxybenzoic acid solvate - Paz, Filipe A. Almeida (2012)
The title compound, C16H36N+ C7H5O4 ÿ C7H6O4 or (nBu4N)+ (2,6-dhb) ÿ (2,6±Hdhb) [where (nBu4N) is tetrabutylammonium, (2,6-dhb) ÿ is 2,6-dihydroxybenzoate and (2,6-Hdhb) is 2,6-dihydroxybenzoic acid], crystallizes in the space group P1. The crystal structure involves alternate layers, in the c direction, of cationic [nBu4N]n n+ and anionic [(2,6- dhb)(2,6-Hdhb)]n nÿ . Hydrogen bonds within the anionic layers form bridges between 2,6-Hdhb and 2,6-dhb ÿ residues.